Effect of non-pharmacological interventions on chemotherapy induced delayed nausea and vomiting for tumors: A systematic review and Bayesian network meta-analysis - Yongni Wang; Fang Wang; Feifei Hu; Fang Long (Complementary Therapies in Medicine)
Objective: To evaluate the efficacy of non-pharmacological interventions in improving chemotherapy induced delayed nausea and vomiting symptoms using a network meta-analysis. Methods: Four Chinese databases (CNKI, Wanfang Data Knowledge Service Platform, VIP, Sinomed) and five English databases (PubMed, Cochrane Library, Embase, Web of Science, CINAHL) were searched from the establishment of the database to April 2024. A Bayesian network meta-analysis was performed on the response rate to the improvement of chemotherapy induced delayed nausea and vomiting, as well as improvement in KPS score, under different non-pharmacological interventions by using R 4.4.0 software and the GeMTC package. Results: A total of 58 RCTs 4081 patients were selected, involving 14 non-pharmacological interventions. The results of Meta-analysis showed that acupoint patch was identified as the most probable superior intervention in the improvement of chemotherapy induced delayed nausea and vomiting, and acupuncture was identified as the most probable superior intervention on the improvement of KPS scores. Conclusion: Non-pharmacological interventions can serve as an effective complementary approach to managing delayed chemotherapy-induced nausea and vomiting. In particular, acupoint application may be the optimal complementary therapy to mitigate the incidence of delayed nausea and vomiting, though more high-quality, large-scale evidence is required to conclusively demonstrate the efficacy of acupuncture in enhancing the quality of life for cancer patients.